EXPLORING PUBLIC UNDERSTANDING OF IMMIGRATION REGULATIONS: A PHENOMENOLOGICAL STUDY OF COMMUNICATION EFFECTIVENESS BY DENPASAR CLASS I IMMIGRATION OFFICE - Yufi Adriani; Rita Kusuma Astuti (Jurnal Abdimas Imigrasi, 2023)
This study aims to explore an in-depth understanding of the experiences and interpretations of the community regarding the socialization process of immigration rules and procedures carried out by the Immigration Office Class I TPI Denpasar. Using a phenomenological approach, in-depth interviews were conducted with a number of individuals from various backgrounds to identify variations in understanding, perception, and reactions to the information provided by the immigration office. The research findings illustrate the diversity in how people interpret immigration socialization, the differing expectations of the process, and the emotional impact and varying levels of adherence. Recommendations for improvements in the outreach approach were also found based on these findings. The results of this study contribute to a deeper understanding of people's perspectives on immigration, with the potential to increase effectiveness and better interaction between the Immigration Office Class I TPI Denpasar and the community.